FAKTOR – FAKTOR YANG MEMPENGARUHI TURNOVER INTENTION KARYAWAN PADA PT. XYZ - HANIFFA, MIRA; RUSWIDIONO, R WASISTO (E-Jurnal Manajemen Trisakti School of Management (TSM), 2024)
The aim of this research is to analyze and determine the influence of organizational commitment, job satisfaction, and job stress on employee turnover intention. This research was conducted at PT. XYZ located in Nambo Udik, Cikande District, Serang Regency, Banten.The research was conducted using descriptive and causality research.  The population used was 73 employees and the sample used was 60 permanent employees using a purposive sampling technique. Data collection techniques include distributing questionnaires using a Likert Scale. Based on the result of data analysis and hypothesis testing, this research shows that job satisfaction has an effect on employee turnover intentions, organizational commitment and job stress has no effect on employee turnover intentions at PT. XYZ.